Short-term predicted extinction of Andean populations of the lizard Stenocercus guentheri (Iguanidae: Tropidurinae) - Andrango Vallejos María Belén (2015)
We studied the thermal physiology of the Andean lizard Stenocercus guentheri in order to evaluate the possible effects of global warming on this species. We determined the preferred body temperature (Tpref), critical thermals (CTmin, CTmax), and hours of restriction and activity. Tpref was 32.14 ± 1.83 °C; CTmin was 8.31 °C in adults and 9.14 °C in juveniles, whereas CTmax was 43.28 °C in adults and 41.68 °C in juveniles. To assess extinction risk, we used the model created by Sinervo et al. (2010) and predicted that 16.7% of the population will have a high risk of extinction by 2020, with an increase to 26.7% by 2050. These results suggest that this species, despite being able to maintain its Tpref through behavioral thermoregulation and habitat selection, could be physiologically sensitive to climate warming; thus, the potential for local adaptation may be limited under a warmer climate. Further studies focusing on the ability of S. guentheri to evolve higher Tpref and thermal tolerances are needed to understand the ability of this species to respond to climate change.